1989
DOI: 10.1002/jor.1100070110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of primate vascularized vs. nonvascularized patellar tendon grafts; changes over time

Abstract: Summary: Mechanical properties of patellar tendon autografts used to replace the anterior cruciate ligament (ACL) in the cynomolgus monkey were measured at four time periods up to l year. The ACL was replaced in each knee with the medial half of the patellar tendon: as a vascularized graft (VG) on one side and as a nonvascularized or free graft (FG) on the other. Postoperative care consisted of 4 weeks of cast immobilization at 30" flexion followed by unrestricted activity in a large cage. Both grafts showed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(108 citation statements)
references
References 33 publications
2
104
2
Order By: Relevance
“…The mechanical properties of tendon autografts are reduced after surgery, and the properties remain abnormal even a year post-operatively [5,6]. Therefore, a goal in ligament reconstruction is to prevent graft deterioration *Corresponding author Tel ' +81-11-706-7211, fax +81-11-706-1822.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of tendon autografts are reduced after surgery, and the properties remain abnormal even a year post-operatively [5,6]. Therefore, a goal in ligament reconstruction is to prevent graft deterioration *Corresponding author Tel ' +81-11-706-7211, fax +81-11-706-1822.…”
Section: Introductionmentioning
confidence: 99%
“…Repositioning the ACL tibial insertion posterior [3] or into the joint [16] reduced ligament strength and increased joint AP translation postoperatively. No study has investigated if increased initial graft laxity also affects the subsequent graft strength and joint stability of ACL reconstructions.…”
Section: Introductionmentioning
confidence: 99%
“…An overall concern during this phase is evidence that the autograft itself is reaching its weakest point structurally during the 6 to 8 week time frame postoperatively [16]. Additional evidence states that the actual graft may only reach between 11 and 50% failure loads of the native ACL at the 1-year point [17].…”
Section: Phase Iii: Postoperative 6 Weeks-3 Monthsmentioning
confidence: 99%
“…Following early necrosis the process of revascularization begins. This usually starts at approximately weeks 6-8 at which time animal studies have shown that the graft is at its weakest point in the post reconstruction process [16]. Some studies indicate that the graft may only reach failure loads of 11 to 50% at 1 year post-operative [17].…”
Section: Introductionmentioning
confidence: 99%